Engineering Mammalian Designer Cells for the Treatment of Metabolic Diseases. Issue 5 (29th November 2017) - Wang, Yidan; Wang, Meiyan; Dong, Kaili; Ye, Haifeng
Abstract : Synthetic biology applies engineering principles to biological systems and has significantly advanced the design of synthetic gene circuits that can reprogram cell activities to perform new functions. The ability to engineer mammalian designer cells with robust therapeutic behaviors has brought new opportunities for treating metabolic diseases. In this review, the authors highlight the most recent advances in the development of synthetic designer cells uploaded with open‐ or closed‐loop gene circuits for the treatment of metabolic disorders including diabetes, hypertension, hyperuricemia, and obesity, and discuss the current technologies and future perspectives in applying these designer cells for clinical applications. In the future, more and more rationally designed cells will be constructed and revolutionized to treat a number of metabolic disorders in an intelligent manner. Abstract : Synthetic biology‐inspired therapeutic strategies relating the engineering of gene circuits in mammalian cells provide new opportunities for treating metabolic diseases. This paper reviews the most recent advances and future perspectives in the development of synthetic designer cells uploaded with open‐loop gene circuits or closed‐loop gene circuits to produce the appropriate drug proteins for treating various diseases by encapsulation. In the future, more and more rationally designed cells will have a deep impact on the revolutionized treatment of a number of metabolic disorders in an intelligent manner.